Rural and Urban Teachers: Differences in Attitudes and Self Concepts - Landa L. Trentham; Barbara B. Schaer (Journal of Research in Rural Education, 1985)
This study investigated the differences in self concept scores and job-related attitude scores of rural and urban teachers. A stratified random sample of rural teachers (N= 339) and urban teachers (N= 245) in a southern state took both the TENNESSEE SELF CONCEPT SCALE (TSCS) and the PURDUE TEACHER OPINIONNAIRE (PTO). Discriminant analysis was used to determine which sub-test scores from the two instruments were significant in differentiating the two groups. Results indicated that the two groups of teachers were significantly different on four sub-scores of the PTO including Curriculum Issues, Rapport Among Teachers, Teacher Salary, and Teacher Load. Rural teachers were more satisfied with Rapport and Load, while urban teachers were more satisfied with Curriculum and Salary. In terms of TSCS sub-scores, rural teachers had significantly higher scores on Moral-Ethical Self, while urban teachers had significantly higher scores on Self-Criticism and Social Self.